N '-(2,5-Dihydroxybenzylidene)benzenesulfonohydrazide - Ali, Hapipah Mohd; Ng, S.W.; Rizal, M.R.; Yusnita, J. (International Union of Crystallography, 2008)
In the title compound, C13H12N2O4S, the dihedral angle between the two aromatic rings is 89.5(1)degrees. In the crystal structure, molecules are linked by O-H center dot center dot center dot O-hydroxy and N-H center dot center dot center dot O-sulfonyl hydrogen bonds, forming a ribbon that propagates along the b axis; there is also an intramolecular O-H center dot center dot center dot N hydrogen bond.